Metode Pelaksanaan Pekerjaan Rigid Pavement Pada Proyek Preservasi Jalan Raya Kanor - Putra Sanjaya (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2023)
Transportation is one part of human needs and interests caused by the movement of objects from one place to another, both in the form of people and goods, which is increasing every day. Roads are land transportation infrastructure that plays an important role in human life. Good road conditions will facilitate the flow of goods and services. Therefore, it is necessary to build and improve roads to facilitate traffic around.